2001
DOI: 10.1159/000051885
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pantoprazole 20 mg to Ranitidine 150 mg b.i.d. in the Treatment of Mild Gastroesophageal Reflux Disease

Abstract: Background: Despite a high prevalence of mild gastroesophageal reflux disease (GERD), few studies investigated efficacy and safety of proton pump inhibitors in this indication. This randomized double-blind study compares pantoprazole to ranitidine in GERD 0 and I, i.e. reflux without esophagitis or with confined lesions only. Methods: Patients received either pantoprazole 20 mg o.a.d. or ranitidine 150 mg b.i.d. Outcome was assessed after 2 and 4 weeks. Primary criterion was relief of leading symptoms, i.e. he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…The relief rates from key GERD symptoms noted in this current study were slightly lower than those reported in other studies comparing pantoprazole 20 mg once daily with ranitidine 300 mg once daily [11, 22]or 150 mg twice a day [23]. For example, in one study evaluating relief from heartburn, acid eructation, and pain on swallowing [22], on day 14 some 69% of the ITT patients receiving 20 mg pantoprazole (once daily in the morning) had achieved relief versus 48% of the patients receiving 300 mg ranitidine (once daily in the evening), with relief rates rising to 80 and 65% for pantoprazole and ranitidine, respectively, on day 28.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…The relief rates from key GERD symptoms noted in this current study were slightly lower than those reported in other studies comparing pantoprazole 20 mg once daily with ranitidine 300 mg once daily [11, 22]or 150 mg twice a day [23]. For example, in one study evaluating relief from heartburn, acid eructation, and pain on swallowing [22], on day 14 some 69% of the ITT patients receiving 20 mg pantoprazole (once daily in the morning) had achieved relief versus 48% of the patients receiving 300 mg ranitidine (once daily in the evening), with relief rates rising to 80 and 65% for pantoprazole and ranitidine, respectively, on day 28.…”
Section: Discussioncontrasting
confidence: 83%
“…For example, in one study evaluating relief from heartburn, acid eructation, and pain on swallowing [22], on day 14 some 69% of the ITT patients receiving 20 mg pantoprazole (once daily in the morning) had achieved relief versus 48% of the patients receiving 300 mg ranitidine (once daily in the evening), with relief rates rising to 80 and 65% for pantoprazole and ranitidine, respectively, on day 28. Another study [23]reported similar relief rates of 69 and 80% on days 14 and 28, respectively, for 20 mg pantoprazole.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the meta-analysis of 6 randomized trials in which H2RA and placebo were compared, the incidence of all of the adverse effects was similar among the arms (RR: 1.13, 95% CI: 0.97-1.31) (39)(40)(41)(42)(43)(44). In the meta-analysis of 8 randomized trials that compared PPI and H2RA, no difference was found between the two groups of drugs in terms of all of the adverse effects (RR: 0.94, 95% CI: 0.86-1.02) and serious adverse effects (RR: 0.93, 95% CI: 0.85-1.01) (39,(45)(46)(47)(48)(49)(50)(51).…”
mentioning
confidence: 99%